(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
The study aims to reveal the level of language social use among children with autism spectrum disorder (ASD) in Jordan and its relationship to some selected variables. The study sample consisted of (120) children, divided into (92) males and (28) females, and their ages ranged from (10-20 years), while the social use scale was applied to reach the results. The results showed that the language social use was at moderate level, where the variable “The language use for different reasons” came in the first rank with an arithmetic mean (1.90) at a moderate level. The second rank was for the variable “Following the rules of conversations and storytelling” with an arithmetic average (1.52) at a moderate level, while the last rank was for the variable “Adapting language to meet the listener’s needs and the situation” with an arithmetic mean (1.47) at a moderate level. Moreover, there were no statistically significant differences at the level of (α = 0.05) in the total score and all variables of the social use scale of language according to the gender variable. In addition, there were significant differences at the level of (α = 0.05) in all dimensions of the Language Social Use scale between the moderate disability category and the severe disability category, where the arithmetic mean of the moderate disability category was greater than the arithmetic means of the disability category.